2005
DOI: 10.1029/2004jd005402
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of HO2 uptake to aqueous aerosol: Mass accommodation coefficients and net reactive loss

Abstract: [1] We present room temperature measurements of HO 2 uptake to aqueous submicron aerosol obtained with an entrained aerosol flow tube coupled to a chemical ionization mass spectrometer. Two aqueous aerosol types were examined, H 2 SO 4 at 35-40% relative humidity (RH) and (NH 4 ) 2 SO 4 at 40-45% RH. By doping the aerosol with Cu(II) ($0.1 M in aerosol) to create an efficient aerosol sink, we determine lower limits to the mass accommodation coefficient, a HO2 , to be 0.8 ± 0.3 for H 2 SO 4 and 0.5 ± 0.1 for (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(165 citation statements)
references
References 34 publications
(86 reference statements)
9
156
0
Order By: Relevance
“…Future experiments using the entrained aerosol flow reactor can and will likely include: i) measurement of the gas-phase reactivity of NO 3 to fully investigate nocturnal nitrogen processing, ii) determination of the ClNO 2 yield following uptake of N 2 O 5 on chloride containing particles (McNeill, et al, 2006;Thornton and Abbatt, 2005b), and iii) investigation of the reactivity of other trace gases of tropospheric significance (e.g., HO 2 , HNO 3 , HOBr) on ambient particles (Thornton and Abbatt, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments using the entrained aerosol flow reactor can and will likely include: i) measurement of the gas-phase reactivity of NO 3 to fully investigate nocturnal nitrogen processing, ii) determination of the ClNO 2 yield following uptake of N 2 O 5 on chloride containing particles (McNeill, et al, 2006;Thornton and Abbatt, 2005b), and iii) investigation of the reactivity of other trace gases of tropospheric significance (e.g., HO 2 , HNO 3 , HOBr) on ambient particles (Thornton and Abbatt, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…These values are not consistent and range from > 0.1 to < 0.01 (Cooper and Abbatt, 1996;Thornton and Abbatt, 2005;Hanson et al, 1992;Gershenzon et al, 1995). The most recent measurement of γ (HO 2 ) on aqueous-phase sulfuric acid aerosols was conducted at 35 % RH (Thornton and Abbatt, 2005).…”
Section: Comparison Of γ (Ho 2 ) With Literature Valuesmentioning
confidence: 99%
“…O − 2 can form on surfaces via direct surface-oxygen electron transfer, photo-induced electron transfer, surface intermolecular electron transfer or decomposition of hydrogen peroxide (H 2 O 2 ) (Anpo et al, 1999). The dissociation of HO 2 to O − 2 occurs in bulk liquid (pK a = 4.7; Thornton and Abbatt, 2005); however, water surrounding the particles only begins to acquire liquidlike properties once the coverage of water is greater than ∼ 2 monolayers. If significant formation of O − 2 does occur above ∼ 2 monolayers of H 2 O, then, owing to its much higher reactivity, some deviation from linearity of γ (HO 2 ) versus monolayers of water (Fig.…”
Section: Tomcat Model Descriptionmentioning
confidence: 99%
“…There are few available measurements of uptake coefficient of HO 2 to salt solutions typical of the marine boundary layer. Thornton and Abbatt (2005) measured reactive uptake coefficients of HO 2 to deliquesced sulphuric acid and ammonium sulphate particles and showed that the loss was not first order in HO 2 . They also estimate that at typical tropospheric concentrations of HO 2 overall reaction probabilities with the aerosol types at room temperature would be much less than 0.01.…”
Section: Diffusion Limitations To Mass Transfer Of Trace Gases To Parmentioning
confidence: 99%